Result Analysis Of Treatment Planning System Between 3-Dimensional Conformal Radiation Therapy Technique And Intensity Modulated Radiation Therapy Technique In Nasopharyngeal Cancer Cases - Nursama Heru Apriantoro; Bambang Sutrisno Wibowo; Muhammad Irsal; Prima Chintya Delsi Kasih (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2017)
This study aims to analyze the difference in results between TPS 3D-CRT radiotherapy irradiation technique and IMRT radiotherapy irradiation technique in nasopharyngeal cancer cases based on the doses received by the target volume and organs at risk and results of isodosis curve which include the value of the index conformity and homogeneity index value. Type of this research is quantitative experimental method. As for the population was taken in 10 patients consisting of 5 male and 5 female patients with nasopharyngeal cancer who received radiation therapy with 3D-CRT irradiation technique and IMRT radiation technique. Meaningfully, the results shows that are no difference in the dose received by the target volume, the dose received by organs at risk, and the curve isodose on these two techniques, including index values of conformity and homogeneity index. In conclusion, IMRT radiotherapy irradiation technique for nasopharyngeal cancer is more prioritized than 3DCRT radiotherapy irradiation technique, as the radiotherapy principle can be achieved by using IMRT radiotherapy irradiation technique.